A techno-economic analysis of biochar production and the bioeconomy for orchard biomass. (November 2021) - Nematian, Maryam; Keske, Catherine; Ng'ombe, John N.
Highlights: Biochar may facilitate a circular bioeconomy for agricultural waste. Stochastic cost modeling is used to evaluate uncertainty in cost estimations. Production costs ∼$448.78–$1, 846.96 (USD) Mg −1 biochar. A biochar enterprise budget is provided as supplemental material. Indirect and induced regional economic benefits are shown. Abstract: It is well established that the global practice of burning crop residues, such as orchard biomass, harms human health and the environment. A bioeconomy for orchard biomass may reduce open burning, facilitate the recovery of nutrients that improve soil health, and boost economic growth. We present a techno-economic analysis for converting orchard waste into biochar, a charcoal-like substance that shows promise for improving soil health, but that is considered an experimental product with emerging efficacy and limited market demand. We impute values derived from a cost analysis of biochar production in California's Central Valley into a regional economic input-output model to demonstrate economic growth and a bioeconomy for biochar made with orchard waste. Results from a stochastic Monte Carlo simulation show a probable range of biochar production costs between $448.78 and $1, 846.96 (USD) Mg −1, with 90% probability that costs will range between $571 and $1, 455 Mg −1 . A sensitivity analysis shows that production costs are most responsive to biochar production rates. A modifiable Excel-based biochar enterprise budget that includes fixed and variable biochar production costs is provided as Supplementary Material. The regional economic analysis demonstrates positive economic growth as defined by job creation, labor compensation, value-added product, and gross output. Stochastic cost estimates and net positive regional economic impacts support economic feasibility of a circular bioeconomy for waste orchard biomass when coupled with governmental policy initiatives. Results may contribute to developing a circular bioeconomy for biochar and orchard biomass in the study region and elsewhere in the world.